2011
DOI: 10.1016/j.aenj.2010.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami preparedness of people living in affected and non-affected areas: A comparative study in coastal area in Aceh, Indonesia

Abstract: The aims of this descriptive comparative study are to describe the levels of tsunami disaster preparedness of people living in areas affected and nonaffected by the December 2004 tsunami, and to compare the tsunami disaster preparedness of these two groups of people. A total of 304 subjects were recruited using a multistage-stratified random sampling from both of the areas along the west coast of Aceh Province. The Individual's Tsunami Preparedness Questionnaire was developed by the researcher and validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
1
8
0
6
Order By: Relevance
“…Likewise, catastrophes from a tsunami, a massive wave caused by undersea earthquakes, can be mitigated or avoided through effective warning systems. Indeed, the catastrophic loss of the Indian Ocean Tsunami of December 2004 was largely due to the absence of warning systems, lack of knowledge, and lack of preparedness among the populations at risk (Rachmalia et al 2011).In contrast, in Japan's Tohoku earthquake on 11 March 2011, the effectiveness of local emergency warning systems and disaster preparedness among Japanese citizens saved many lives, despite the short time between the quake and the tsunami. These examples illustrate that personal disaster preparedness is critical to mitigate disaster impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, catastrophes from a tsunami, a massive wave caused by undersea earthquakes, can be mitigated or avoided through effective warning systems. Indeed, the catastrophic loss of the Indian Ocean Tsunami of December 2004 was largely due to the absence of warning systems, lack of knowledge, and lack of preparedness among the populations at risk (Rachmalia et al 2011).In contrast, in Japan's Tohoku earthquake on 11 March 2011, the effectiveness of local emergency warning systems and disaster preparedness among Japanese citizens saved many lives, despite the short time between the quake and the tsunami. These examples illustrate that personal disaster preparedness is critical to mitigate disaster impacts.…”
Section: Introductionmentioning
confidence: 99%
“…3). The scar of this rockslide, just a few miles outside Lyngseidet, could be seen by schools directly in the field, because indirect experience with a past tsunami increases the awareness of people in as yet unaffected areas (Rachmalia et al 2011). A survey conducted in Norway into rockslide tsunami risk also showed that those people who were willing to follow evacuation instructions lived in places where identical disasters had already occurred (Rød et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Two examples of more practically useful definitions are "Tsunami preparedness refers to an individual's perception of the extent of being prepared to confront with future tsunami." (Rachmalia et al 2011) and "Strategic preparedness connotes a set of policies, plans, and supporting infrastructure that is implemented in advance of a natural or man-made disaster." (Haimes et al 2008).…”
Section: Preparedness Definitionsmentioning
confidence: 99%
“… (Personal) tsunami preparedness: Knowledge, individual emergency planning and resource mobilization capacity (Rachmalia et al 2011).  (Personal) hurricane preparedness: Food for three days, flashlight with batteries for three days, medicines, drinkable water, important papers on hand, an outdoor grill, a generator (Baker 2011).…”
Section: Select Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation